Flow regimes and thermal characteristics in air conditioned office : Personalized ventilation versus underfloor supply - Mohammed Abdelsalam Abdelhamid Ali; Essam Eldin Khalil; Gamal Abdelmoneim Elhariry; Hesham Abdelgaffar Othman (Cairo : Mohammed Abdelsalam Abdelhamid Ali, 2013)
This research uses computation fluid dynamics CFD to study the effect of personalized ventilation (PV) in conjunction with underfloor air distribution system (UFAD) and study the distribution of carbon dioxide COb2 (Bcontaminant concentrations in the air - cnditioned office. The present work also investigates the characteristics of underfloor air distribution system (UFAD) system and compare with ceiling supply mixing ventilation(CSMV)s
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Mechanical Power Engineering
Issued also as CD
Keywords: Indoor air quality; Personalized ventilation; Thermal comfort